2018
DOI: 10.1186/s12864-017-4428-5
|View full text |Cite
|
Sign up to set email alerts
|

Unique, dual-indexed sequencing adapters with UMIs effectively eliminate index cross-talk and significantly improve sensitivity of massively parallel sequencing

Abstract: BackgroundSample index cross-talk can result in false positive calls when massively parallel sequencing (MPS) is used for sensitive applications such as low-frequency somatic variant discovery, ancient DNA investigations, microbial detection in human samples, or circulating cell-free tumor DNA (ctDNA) variant detection. Therefore, the limit-of-detection of an MPS assay is directly related to the degree of index cross-talk.ResultsCross-talk rates up to 0.29% were observed when using standard, combinatorial adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
154
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(159 citation statements)
references
References 23 publications
1
154
0
Order By: Relevance
“…To determine whether BGISEQ-500 sequencing accuracy is affected by index hopping, as occurs with Illumina's sequencers 3,4,[8][9][10][11] , we examined the rate of index mis-assignment in BGISEQ-500 runs. We ligated eight unique single indexes to eight gene regions, respectively (indexes 1-8) ( Supplementary Table 1) or to eight water controls lacking DNA inputs (indexes 33-40), and we pooled equal volumes of all samples after PCR amplification.…”
Section: Index Mis-assignment In Controlsmentioning
confidence: 99%
“…To determine whether BGISEQ-500 sequencing accuracy is affected by index hopping, as occurs with Illumina's sequencers 3,4,[8][9][10][11] , we examined the rate of index mis-assignment in BGISEQ-500 runs. We ligated eight unique single indexes to eight gene regions, respectively (indexes 1-8) ( Supplementary Table 1) or to eight water controls lacking DNA inputs (indexes 33-40), and we pooled equal volumes of all samples after PCR amplification.…”
Section: Index Mis-assignment In Controlsmentioning
confidence: 99%
“…To address these issues, we performed library barcoding with dual unique indexes. 32 Tru-seq HT style combinatorial indexing using D7xx/D5xx pairs resulted in a median contamination of 0.5% (maximum 8.9%).…”
Section: Ultra-rare Variant Calls Enabled By Qctsmentioning
confidence: 99%
“…However, as several studies have recently shown (Sinha et al, 2017;Costello et al, 2018), multiplexing leads to incorrect sample assignment of a significant fraction of demultiplexed sequencing reads. Out of several mechanisms that can introduce sample index missassignment (MacConaill et al, 2018), the presence of free-floating indexing primers that attach to the pooled cDNA fragments just before the exclusion amplification step in patterned sequencing flowcells has been shown to be the main culprit (Illumina, 2017). This phenomenon is known as sample index hopping and results in a data cross-contamination artifact that takes the form of phantom molecules, molecules that exist only in the data by virtue of read misassignment (Figure 1a).…”
Section: Précismentioning
confidence: 99%
“…Unfortunately, sample multiplexing can cause a significant percentage of the demultiplexed sequenced reads to be misassigned to an incorrect sample barcode. Although sample read misassignments can arise due to several factors (MacConaill et al, 2018), one specific mechanism termed sample index hopping is the primary cause of read misassignments in patterned flow cells. Index hopping is believed to result from the presence of free-floating indexing primers that attach to the pooled cDNA fragments just before the exclusion amplification step that generates clusters on the flow cell.…”
Section: Overview Of Sample Index Hopping On Illumina's Sequencersmentioning
confidence: 99%